PERILAKU KONSUMEN DAN STRATEGI PENGEMBANGAN AGROINDUSTRI BERAS SIGER TUNAS BARU DI KELURAHAN PINANG JAYA KEMILING KOTA BANDAR LAMPUNG - Windi Ariesta; Dyah Aring Hepiana Lestari; Wuryaningsih Dwi Sayekti; R Hanung Ismono (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
This research aims to analyze consumen’s behavior and strategies in the development of siger rice agroindustry. This research used a case study method.The samples are stakeholder on agroindustry and consumen of siger rice. Technique sampling for consumers is snowballing.  The method of data analyzes used descriptive analysis and SWOT analysis. The results of this research showed that: The consumen’s satisfaction that seen from the repay of siger rice product and consumers have information and knowledge about the characteristics of siger rice, Combination value IFE was 0.19 and value of EFE was-0.05 in the IE matrix shows that the position the businessin quadran II. Its mean the agroindustry are in the a readiversification. The best priority strategies for developing the agroindustry are in creasing the capital of agroindustry from agroindustry fund and government institutions to fullfill the demand of siger rice.                                                                                                                        Key words: consumen, development strategy, siger rice, SWOT analysis